Roll of thunder, hear my cry - Taylor, Mildred D. (New York : Dial, 1976)
An African-American family living in the South during the 1930s is faced with prejudice and discrimination which its children don't understand.
Sequel: Let the circle be unbroken.
Wilson's Children, November 1996.
Wilson's Junior High School, September 1995.
Elem. School Library Collection, June 2000.
Notable/Best Books (A.L.A.), January 1977.
School Library Journal, October 2010.
Keywords: African Americans -- Fiction; African Americans -- Fiction; African Americans -- Fiction; Race relations -- Fiction; Kurzweil format available; Southern States -- Race relations -- Fiction; Southern States -- Race relations -- Fiction; Southern States -- Fiction